Improving the System for Evaluating the Efficiency and Performance of Civil Servants - A. A. Bakulina; N. A. Zavalko; N. L. Krasyukova (Управленческие науки)
This article addresses the pressing issue of improving the system for evaluating the efficiency and performance of civil servants within the context of public administration development and enhancing the quality of public services. The aim of the study is to develop proposals for modernizing the existing evaluation system for civil servants based on a fundamental analysis of theoretical approaches, domestic practices, and international experience. The work presents a comprehensive analysis of both the key categories and approaches used in this field, as well as the current regulatory and legal framework. The current state of Russia’s civil servant evaluation system is examined, revealing key issues such as procedural formalism, subjectivity, weak connection with HR processes, insufficient evaluator competence, and underdeveloped information and analytical systems. Advanced international practices in civil servant evaluation are reviewed, including those in the United States, the United Kingdom, Germany, France, and Canada. The article proposes main directions for improvement: the implementation of results-based management using key performance indicators (KPIs); the development of a competency-based approach; digitalization of evaluation procedures; and strengthening the link between evaluation outcomes and motivation mechanisms. The study’s methodology is grounded in scientific methods such as analysis and synthesis. The results can be used in the modernization of the civil servant evaluation system, as well as in the development of legal and methodological documents in this field.